Are protected areas good for the human species? Effects of protected areas on rural depopulation in Spain - Rodríguez Rodríguez, David; Larrubia-Vargas, Remedios; Ruiz-Sinoga, José Damián (Science of The Total Environment, 2021)
Protected areas (PAs) seek to conserve valuable genes, species and ecosystems by applying a legal regime that restricts some socioeconomic activities and also offers opportunities for new ones. As a result, PAs have been claimed by some authors to boost socioeconomic conditions in rural areas mainly through tourism activities. However, others have claimed that PAs contribute to rural depopulation through the worsening of living conditions of local residents because of restrictions resulting from protection regulations. Here, we applied a multiple-paired Before-After-Control-Impact (BACI) research design on a census on protected rural municipalities (cases; N = 52) versus unprotected rural municipalities (controls; N = 55) in Spain to ascertain whether PAs had positive or negative effects on rural populations using three indicators on depopulation with official municipal data from 1996 until 2019: Compound annual growth rate (CAGR); Proportion of reproductive individuals (REP); and Proportion of reproductive females (WREP). We controlled for some confounders such as biophysical characteristics and regional regulations by carefully selecting our sample of municipalities spatially. Our results show that depopulation figures were worse in cases than in controls, with some exceptions whose characteristics should be further explored. Municipalities in Sites of Community Importance (SCIs) performed best against rural depopulation and generally better than their controls, whereas municipalities in Biosphere Reserves and Special Protection Areas (SPAs) showed mostly worse figures. Our findings suggest that, while necessary and important for biodiversity, multiple-use PAs generally entailed negative consequences for Spanish rural populations that need to be offset by State's intervention.
Keywords: Desarrollo rural; Despoblación; Áreas protegidas; Desarrollo rural